Pathogenic Role of Circulating Citrullinated Antigens and Anti-Cyclic Monoclonal Citrullinated Peptide Antibodies in Rheumatoid Arthritis - Won, Pureun; Kim, Youngkyun; Jung, Hyerin; Rim, Yeri Alice; Sohn, Dong Hyun; Robinson, William H.; Moon, Su-Jin; Ju, Ji Hyeon (Frontiers in Immunology, 2021)
We examined whether it is possible to directly detect citrullinated antigens in the serum of rheumatoid arthritis (RA) patients using a monoclonal antibody (mAb) designed to be specific for citrullinated peptide. In order to confirm the potential of mAb as a direct arthritis-inducing substance through experimental model of RA, a monoclonal antibody (mAb) 12G1 using hybridoma method by challenging cyclic citrullinated peptide was generated. Immunohistochemical analysis of RA-affected synovial tissue showed that our synthetic mAb 12G1 could indeed detect citrullinated proteins in target tissues. Subsequently, Serum levels of citrullinated type II collagen, and filaggrin were measured in healthy volunteers, patients with RA, ankylosing spondylitis (AS), and systemic lupus erythematosus (SLE) using an 12G1-based sandwich ELISA. ELISA showed that citrullinated filaggrin showed 78.9% sensitivity and 85.9% specificity for RA diagnosis with a cutoff OD value of 1.013, comparable with the results from a second-generation ACPA test. Circulating citrullinated collagen and filaggrin were detected even in sera of RA patients who were negative for both rheumatoid factor (RF) and ACPA. ELISA results also showed that RF and ACPA titers showed significantly positive correlation with both citrullinated collagen and filaggrin optical density (OD) value in sera of RA patients. 12G1 challenging aggravated severity of murine arthritis. In summary, mAb 12G1 can directly detect citrullinated proteins in RA target tissue and in sera of RA patients. 12G1 showed direct arthritogenic potential in vivo. 12G1 might be useful for diagnosis of RA including seronegative RA and may help to elucidate the pathophysiological role of citrullination in RA.